The relationship between urinary organophosphate pesticide residues and reproductive development among boys living in the rural Western Cape - Monate, Pearl Naledi (Department of Public Health and Family Medicine, 2019)
Background: Many contemporary agricultural pesticides are hormonally active, but few previous studies have investigated their effect on the reproductive health and growth of pubertal boys. A previous analysis found significant differences in serum reproductive hormone levels and lower anthropometric measurements as well as non-significant lower sexual maturity ratings and testicular sizes in farm boys compared to non-farm boys from the rural Western Cape in South Africa. Methodology: This analysis included 183 out of 269 school boys residing on farms and neighbouring nonfarming areas who provided urine samples in a cross-sectional study. Measurements included a questionnaire, clinical assessment of sexual maturity development (SMD), anthropometric measurements (height, weight and body mass index (BMI)), serum reproductive hormones (including luteinizing hormone (LH), follicle stimulating hormone (FSH), testosterone and oestradiol (E2)) and urinary levels of 3 dialkyl phosphates (organophosphate pesticide metabolites) including di-ethyl, di-methyl and di-methyl triphosphate (DEP, DMP and DMTP). Results: The median (interquartile range) of age and sum dialkyl phosphates of the school boys was 12 years (9-13 years) and 68.3 ng/mL (27.9-129.5 ng/mL) respectively. There were consistent, mostly non-significant associations with some dose response relationships between urinary levels of dialkyl phosphates and adverse effects on outcomes including SMD, serum reproductive hormones and anthropometric development. The strongest results included a strong positive association and dose response found between serum oestradiol > the 50th percentile and quartiles DMTP (odd ratio and confidence interval for highest and lowest quartile: 7.4; 1.7-32.4) and between BMI <50th percentile and quartiles of DMTP (odd ratio and confidence interval for highest and lowest quartile: 3.2; 1.2-9.0). Conclusion: The results provide some preliminary evidence that organophosphate pesticides exposure could alter the reproductive hormone levels and adversely affect the body size of school boys. There was also lack of evidence of other adverse effects on reproductive development. These findings require further investigation in a larger longitudinal study with seasonal bio-monitoring for pesticides.